Determination of Human Hair Components by Spectrophotometric Methods for the Diagnosis of Thyroid Diseases - Fatima H. Salih; Shaimaa S. Mahdi; Alaa H. Ali (مجلة بغداد للعلوم)
Human hair is a vital tissue, rich in minerals and vitamins that have an effective role in the production of enzymes, hormones and other substances necessary for normal growth, it is considered an indicator of any defect in the performance of body functions at all stages of life, so the use of hair in the diagnosis of diseases is a challenge in the clinical laboratory, as it will be easy to frequently monitor diseases, and it will have an impact on medical research and treatment. For instance, hypothyroidism occurs when the thyroid gland does not secrete enough thyroid hormone into the blood. If neglected, it may lead to health problems including high cholesterol and cardiac issues.  In this research, physical techniques were employed to detect hypothyroidism using a single human hair, as the optimal use of science gives an opportunity to consider hair as a tool in diagnosing diseases. Among these modern physical techniques, FTIR and Raman spectral techniques were adapted. The FTIR technique enables the identification of the compounds as well as the difference between people with healthy function and those who have hypothyroidism. Additionally, this approach demonstrated that those with hypothyroidism had high levels of harmful cholesterol. This was proven using the Raman spectral technique, which gave similar and complementary results obtained by the FTIR technique.